2021
DOI: 10.1021/acs.cgd.0c01637
|View full text |Cite
|
Sign up to set email alerts
|

π-Stacking Conversion and Enhanced Force-Stimuli Response of a Divinylanthracene Derivative in a Hydrogen-Bonded Framework

Abstract: Hydrogen bond-induced π-stacking conversion was used to achieve an enhanced force-stimuli response of 9,10-bis­(2-(pyridin-4-yl)­vinyl)­anthracene (BP4VA). In BP4VA crystals, the molecules adopted a J-aggregate pattern, and no overlap between the central anthracene planes was observed. Trimesic acid (TA) as a hydrogen bond donor could promote the transformation of the π-stacking type of BP4VA as a hydrogen bond acceptor. It was found that TA and BP4VA molecules formed two-dimensional lamellar hydrogen-bonded f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 58 publications
(83 reference statements)
0
7
0
Order By: Relevance
“…Through the rational design of organic building blocks with geometric symmetry, planar molecules with diverse π-conjugated systems can coordinate to each other through intermolecular H-bonding interactions to form a single layer, and multiple layers pack together through strong π–π-stacking interactions to form a 3D framework with one-dimensional (1D) channels throughout the structure. HOFs that contain large, π-conjugated aromatic molecules as building blocks exhibit significantly enhanced thermal stabilities and increased chemical resistance to organic solvents and acidic or basic aqueous solutions due to the inert reactivity of the tectons (Figure ) (see refs , , , , , , , , , , , , , , , , , , , , , , , ). Several groups have independently demonstrated that HOFs with shape-fitted π–π-stacking interactions not only show type III stability upon desolvation but also become even more stable as the effective π–π-stacking areas become larger (Table ).…”
Section: Design Rules Of Stable Hofsmentioning
confidence: 99%
“…Through the rational design of organic building blocks with geometric symmetry, planar molecules with diverse π-conjugated systems can coordinate to each other through intermolecular H-bonding interactions to form a single layer, and multiple layers pack together through strong π–π-stacking interactions to form a 3D framework with one-dimensional (1D) channels throughout the structure. HOFs that contain large, π-conjugated aromatic molecules as building blocks exhibit significantly enhanced thermal stabilities and increased chemical resistance to organic solvents and acidic or basic aqueous solutions due to the inert reactivity of the tectons (Figure ) (see refs , , , , , , , , , , , , , , , , , , , , , , , ). Several groups have independently demonstrated that HOFs with shape-fitted π–π-stacking interactions not only show type III stability upon desolvation but also become even more stable as the effective π–π-stacking areas become larger (Table ).…”
Section: Design Rules Of Stable Hofsmentioning
confidence: 99%
“…Light-emitting materials have attracted considerable attention and been widely explored over the past few decades because of their diverse applications in light-emitting diodes, light-harvesting systems, biological sensing, imaging, etc. Interactions of chromophores directly have a significant effect on the photophysical properties of fluorescent materials. Kasha and co-workers provided the theoretical conception of molecular exciton theory in their pioneering work, suggesting that the photophysical properties in the solid state can be largely influenced by interactions between molecular transition dipoles. In some cases, crystals or solids with specific intermolecular interactions of chromophores exhibit tunable fluorescence properties. However, this strategy is diffusion-controlled and intermolecular interactions cannot be maintained when dispersed in solution, which limits the exploration of interaction–property relationships (Scheme a).…”
Section: Introductionmentioning
confidence: 99%
“…Still, all of these materials are not dual-state emissive fluorogens (DSEgens). 9,10 The molecular design of dual-state emitters through isomeric substitution is somewhat realized but is tricky. However, the stimuli-responsive nature of such DSEgens was not always identified.…”
Section: Introductionmentioning
confidence: 99%
“…It is pertinent to mention that multitasking symmetrical systems such as anthracenyl π-conjugates are well-explored as AIE, MFC (mechanofluorochromic), and SSAC-active solid-state emitters in the literature 9 b , c ,14 b due to their easy accessibility, longer conjugation, and twisted molecular structure with numerous intermolecular interactions. 9 In contrast, we focused on investigating relatively smaller asymmetrically substituted anthracenyl π-conjugates that would also attain a twisted molecular system and multiple supramolecular interactions, offering intriguing photophysical features under different environments and displaying potential applications. Further, introducing non-symmetric substituents was reported to be useful in increasing the quantum yield.…”
Section: Introductionmentioning
confidence: 99%